Penggunaan Video Youtube Untuk Meningkatkan Hasil Belajar Seni Musik Pada Siswa Kelas XI SMA Negeri 3 Payakumbuh - Yoffrizal Putra; Yos Sudarman (SENDRATASIK UNP, 2020)
Starting from the problem of music learning which has been developed by the use of the internet and YouTube at SMA Negeri 3 Payakumbuh, the researcher conducted a research with the aim to explain that the use of Youtube videos can improve the learning outcomes of students in XI MIPA-2 of SMA Negeri 3 Payakumbuh.The theory used in this research includes learning and instruction, internet based instruction, instruction done through YouTube videos, use of lecture and presentation methods in instruction, and learning outcomes theory. This is a quantitative research with a true-experiment-design approach. The study population was all students of grade XI, and the sample was class XI MIPA-2 (as the experimental class) and XI MIPA-3 (as the control class). The results of observation, interview, and literature study were used as the research instruments. The results statistically prove that the hypothesis test for H1 is accepted while the null hypothesis H0 is rejected. The data, which can be explained qualitatively, show that YouTube video integrated with the Powerpoint shows used by the researcher in providing music instruction through lecture and presentation is easier to understand.